Legal Protection for Policy Holders of Life Insurance Berhad Bumiputera 1912 Due to Default - Firza Nada Salsabila; Edi Wahjuni; Firman Floranta Adonara (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2025)
Insurance companies in Indonesia, including Life Insurance Together Bumiputera 1912, hereinafter referred to as AJB Bumiputera 1912, continue to innovate to provide the best service to customers. However, problems arise when this company fails to pay claims to policyholders, causing dissatisfaction among customers. The legal protection provided to customers is outlined in the Civil Code, hereinafter referred to as KUHPerdata. The purpose of this research is to understand what legal protection means for policyholders as insured parties of AJB Bumiputera 1912 who suffer losses due to default. This research utilizes a normative juridical method, which involves studying and examining the implementation of the rules and regulations in existing positive law in Indonesia to analyze the South Jakarta District Court's decision regarding default. The conclusion of this research is that legal protection allows customers to file lawsuits in the event of default by the insurance company, such as delays in claim payments. Insurance companies have a legal obligation to pay compensation or cover losses arising from claims filed by policyholders in accordance with applicable provisions. The South Jakarta District Court granted the plaintiff's lawsuit and ordered the defendant to pay the insurance claim, late interest, and court costs. This demonstrates the importance of legal protection for customers in legal relationships with insurance companies to maintain fairness and balance.